Global equity offerings, corporate valuation, and subsequent international diversification - Hasan, Iftekhar; Kobeissi, Nada; Wang, Haizhi (Strategic Management Journal, 2011)
Abstract Researchers have long wondered why U.S. firms offer their equity in multiple global capital markets even though they have access to a deep domestic capital market. Based on a propensity score‐matching sample of IPOs for U.S. firms from 1990 to 2003, this paper offers some potential answers. We find strong evidence that issuers who choose global equity offerings experience higher valuations at the IPO stage, as measured by Tobin's q. Our evidence also shows that global equity offerings serve as a deliberate strategic tool to increase issuers' international visibility and their propensity to diversify operationally to international markets. Copyright © 2010 John Wiley & Sons, Ltd.